Τρία πρόσφατα "Καππαδοκικά" τραγούδια από τη Νέα Σινασό - Δραγούμης, Μάρκος Φ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1984)
In 1962 the Belgian musicologist Paul Collaer, in collaboration with the «M. Merlier Folk Music Archives», recorded among other items, about a dozen songs from a female refugee from Cappadocia in Asia Minor, then living in the northern part of the island of Euboea (Néa Sinassós). The present article examines only those of the above songs which are unknown. All three of them have certain characteristics in common: their texts are recent (late 19th - early 20th centuries) and more or less of an improvisatory nature; they deal with subjects concerning illness, death and the grief of the refugee; and in spite of the interest of their themes and the importance they have for the study of the later stages of the development of Greek folk song, they display certain weaknesses in their phrasing and versification. The relation of N° 1 with a certain type of rébétika (songs of illness) is noteworthy. N° 2, belongs to the category of the so called «incidental» (peristatika) songs, while at the same time it is distantly related to the rébétika of the underworld. Moreover N° 3 is the only dirge (mirológi) from Cappadocia which has come down to us in its complete form, i.e. both with its text and tune. The article is completed by a detailed study of the unfolding patterns of the melodies, their modality, rhythm, architectonic structure and form.